Beauty Standard Construction in Magazine Advertisements - Diyantari; Desiyanti, Niken Monica; Lililacs , Admin (Lililacs Journal, 2022)
This study focuses on the constructed idea of beauty in makeup and skincare advertisements that appears on Women’s Weekly Singapore’s magazine, and Femina, Indonesia’s magazine 2019 edition. The purpose of this study is to know how the idea of beauty are constructed by the makeup and advertisements from both countries throughout magazines advertisements. In order to know how the idea constructed idea of beauty from those advertisements, the writer uses a descriptive- analytical-interpretative method. Furthermore, in doing the analysis, some related theories are employed, namely there are Social Visual Semiotics theory by Gunther Kress and Van Leeuwen, and Systemic Functional Linguistics by M.A.K. Halliday. The result of this study found that Singapore advertisements, promoting the unrealistic beauty conception in terms of visual images, that attract the viewers to achieve the bright skin, as the female portrayed is the white Caucasian female model. While the makeup advertisement from Femina, Indonesia’s magazines portrayed the native female model that is having a light tanned skin, curly hair, black big eyes. She is manifested the Indonesian women figure in general. This idea of beauty also reflected in the written or verbal text which is taglines of this product. This product, however delivering the idea of beauty that is more realistic for most Indonesian women.